Non-Wycliffite Bible Translation in Oxford, Trinity College, 29 and universal history writing in Late Medieval England - Gillhammer, CC (De Gruyter, 2020)
The late-fifteenth-century Middle English manuscript Oxford, Trinity College, 29 contains a universal history of the world, compiled from diverse religious and secular source texts and written by a single compiler-scribe. A great part of the text is focused on Old Testament history and uses the Vulgate as a key source, thus offering an opportunity to examine in detail the compiler’s strategies of translating the text of the Bible into the vernacular. The Bible translations in this manuscript are unconnected to the Wycliffite translations, and are non-reformist in their interpretative framework, implications, and use. This evidence is of particular interest as an example of the range of approaches to biblical translation and scholarship in the vernacular found in late medieval English texts, despite the restrictive legislation concerning Bible translation in fifteenth-century England. The strategies of translating the biblical text found in this manuscript include close word-by-word translation (seemingly unencumbered by anxieties about censorship), as well as other modes of interaction, such as summary, and exegesis. This article situates these modes of engagement with the Bible within a wider European textual tradition of including biblical material in universal history writing.